Dongeng Digital Berbasis Project Based Learning Untuk Penguatan Profil Pembelajaran Pancasila Siswa Sekolah Dasar - Prayuningtyas Angger Wardhani; Gusti Yarmi; Chrisnaji Banidra Yudha (UNIB Press, 2024)
In an effort to improve students' literacy, it is necessary to have learning media that is in accordance with the times. This study aims to determine the level of need for fairy tales in supporting the Pancasila learner profile of elementary school students. The research method to be used in this research is the research and development method of the 4-D model (Four-D Model) with the stages of define, design, development and Disseminate. In this study only at the defining stage, namely conducting a field needs analysis first. Respondents in the study were 30 teachers and 50 students from eight elementary schools in Jakarta. The data collection technique was obtained by distributing a structured questionnaire with a Likert scale to teachers with 2 answer choices and open answers. The aspects used to measure the level of teacher needs include learning objectives, learning stages, learning environment, classroom management, and classroom management. The results showed that teachers have used digital media, but still need to develop digital media that can increase student understanding. In addition, digital fairy tale media also supports the profile of Pancasila students while the results of the analysis of student needs show that the use of digital fairy tale media makes students motivated to participate in learning activities, and can easily understand abstract concepts.